Pengaruh Shoping Lifestyle Gen Z Terhadap Implusif Konsumen Di Tiktok Shop - Rexy Andalangi Maatuil; Levina Anita; Rade, Nayoan; Allya Anjeli Delia Lembang; Dorainda Pristy Riahi; Christifora Novalya Lumikis (Indo Publishing, 2025)
The development of digital technology and the presence of social commerce platforms such as TikTok Shop have changed the shopping patterns of Generation Z in Indonesia. Gen Z is known as the largest TikTok user and is highly responsive to visual content, live streaming, and various promotions, making them more susceptible to impulse buying. This study aims to analyze the influence of shopping lifestyle on impulsive buying among TikTok Shop users aged 13–28 years. The method used is a quantitative approach through a cross-sectional survey with SEM analysis. The results show that shopping lifestyle has a positive and significant influence on the tendency to impulse buy. Perceptions of discounts also mediate this relationship, where promotions such as vouchers and flash sales increase the urge to buy spontaneously. Furthermore, the frequency of TikTok use moderates the influence of shopping lifestyle, so that users with high intensity are more easily driven to buy spontaneously. These findings contribute to the theory of consumer behavior in the digital era.